Wave propagation in a medium with position-dependent permittivity and permeability - Roozbeh, Ashkan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
ABSTRACT: The electromagnetic wave propagation in inhomogeneous media is studied. The wave equation in such a medium is obtained. By considering the permittivity as a positiondependent function (i.e, z-dependent) and the permeability as a constant (i.e, μ=kmμ0) the wave equation is determined. The wave function is reported exactly in a medium with smooth step dielectric constant, in terms of hypergeometric function. The asymptotic behaviors of the wave function are examined and the reflection and transmission coefficients are found in perfect agreement with the previous results. Moreover, a smooth double layer case is studied and the corresponding wave function is presented and plotted exactly in terms of Heun function. Besides, the asymptotic behavior of the wave function is appointed. It is noticeable that the result of this thesis published in an international journal. ………………………………………………………………………………………………………………………… ÖZ: Ayni cinsten (homojen) olmayan bir ortamda elektromagnetik dalga yayılması incelenmi ştir. Böyle bir ortamda dalga denklemi inşa edilmiştir. Magnetik geçirgenlik katsayısı (/mu) sabit, elektrik geçirgenlik katsayısı (/epsilon ) ise z- yönüne bağlı olduğu durumda denklem çözülmüştür. Sürekli tek adım geçişli elektrik parameter durumunda çözüm hipergeometrik fonksiyonlar cinsinden ifade edilmiştir. Kırılma ve geçirme katsayıları önceki homojen durumlardakine indirgenecek şekilde tanımlanmıştır. Çift adım geçişli ortam probleminde ise elektromagnetik dalga Heun fonksiyonları cinsinden kesin olarak bulunmuştur. Asimtotik değerler sayısal incelenip dalga davranışı grafiksel çizilmiştir.
Master of Science in Physics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Physics, 2013. Supervisor: Assist. Prof. Dr. S. Habib Mazharimousavi.
Keywords: Physics; Electromagnetism; Field theory (Physics); Mazharimousavi, Habib